Exploring decision makers' knowledge, attitudes and practices about decentralisation and health resources transfer to local governments in Burkina Faso - Hilaire Zon; Milena Pavlova; Wim Groot (Taylor & Francis Group, 2023)
In the health sector, decentralisation mainly consists of the devolution of administrative functions to local governments. Since 2009, Burkina Faso has engaged in a process to transfer health resources to local governments. This study examines the decision-makers' knowledge, attitudes and practices (KAP) about the decentralisation and health resources transfer to local governments in Burkina Faso. We used a qualitative research method. In-depth semi-structured interviews were conducted with key decision-makers. The data collected went through a directed qualitative content analysis. Findings suggest that all respondents are aware of the rationale of the decentralisation and resources transfer to local governments. The vast majority of respondents have a positive opinion towards decentralisation and the main elements that appear to be motivating their attitude, are the expected outcomes from decentralisation. The practical experience was limited to awareness raising, training, supervision, technical assistance and resources mobilisation. Poor collaboration between health districts and local governments, the control of certain resources by the state and the health districts constrain the implementation of health resources and skills transfer policy at grassroots level. Careful attention should be given to the country's political context and institutional design.